Therapeutic potential of growth differentiation factors in the treatment of degenerative disc diseases. Issue 1 (8th March 2019) - Hodgkinson, Tom; Shen, Bojiang; Diwan, Ashish; Hoyland, Judith A.; Richardson, Stephen M.
Abstract : Intervertebral disc (IVD) degeneration is a major contributing factor to chronic low back pain and disability, leading to imbalance between anabolic and catabolic processes, altered extracellular matrix composition, loss of tissue hydration, inflammation, and impaired mechanical functionality. Current treatments aim to manage symptoms rather than treat underlying pathology. Therefore, IVD degeneration is a target for regenerative medicine strategies. Research has focused on understanding the molecular process of degeneration and the identification of various factors that may have the ability to halt and even reverse the degenerative process. One such family of growth factors, the growth differentiation factor (GDF) family, have shown particular promise for disc regeneration in in vitro and in vivo models of IVD degeneration. This review outlines our current understanding of IVD degeneration, and in this context, aims to discuss recent advancements in the use of GDF family members as anabolic factors for disc regeneration. An increasing body of evidence indicates that GDF family members are central to IVD homeostatic processes and are able to upregulate healthy nucleus pulposus cell marker genes in degenerative cells, induce mesenchymal stem cells to differentiate into nucleus pulposus cells and even act as chemotactic signals mobilizing resident cell populations during disc injury repair. The understanding of GDF signaling and its interplay with inflammatory and catabolic processes may be critical for the future development of effective IVD regeneration therapies. Abstract : This review outlines our current understanding of intervertebral disc degeneration, and in this context, aims to discuss recent advancements in the use of growth differentiation factor (GDF) family members as anabolic factors for disc regeneration. It highlights how the understanding of GDF signalling and its interplay with inflammatory and catabolic processes may be critical for the future development of effective intervertebral disc regeneration therapies.